Penerapan Metode Exponential Smoothing Winters Pada Prediksi Harga Beras - Ria Pertiwi Nugraheni; Elistya Rimawati; Retno Tri Vulandari (Jurnal Ilmiah SINUS, 2022)
Forecasting is an attempt to predict future conditions through testing conditions in the past using previous data. According to the data obtained from Dinas Perdagangan, Koperasi, dan UMKM Sukoharjo in January 2016 - August 2019, the prices of rice in Sukoharjo Regency experienced instability. Based on this problem, a method is needed to predict the price of rice in Sukoharjo Regency to prevent price volatility and to provide an overview of the price of rice in Sukoharjo Regency in the coming period. The method used in this research is the Exponential Smoothing Winters method. The rice price prediction application is made using the vb.net programming language and the sql server database. in this application produces predictive calculations for rice and in it there are graphs and reports on the results of prediction calculations. This study resulted in an overall MAPE of 3.91% for the price of  premium IR 64  rice,  and  4.24% for the price of  medium IR 64 rice.